Bagaimana Mempertahankan Karyawan Berketerampilan Tinggi? Studi Ekstrapolasi Faktor-Faktor Yang Menyebabkan Dosen Meninggalkan Organisasinya - Haludin, Guntur; Naibaho, Hastuti (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: This paper discusses the factors that cause lecturers to resign based on an extrapolation study at a private corporate University located in South Tangerang, Banten region, Indonesia owned by a big business group in Jakarta. Methods: The research was conducted using the data from exit interviews that were done by the HR for people who had left the university during 2020-2021 with a total of 25 respondents and the engagement survey result done for people who were still working in 2022 with a total of 109 respondents. Finding: The results showed that the top three main driving factors for lecturer turnover are remuneration, recognition, and work-life balance. Theoretical contribution/Originality: These findings provide an important contribution in the context of human resource management in higher education, refer to Maslow's needs theory, and emphasize the need to pay attention to these factors. Practitioner/Policy implication: The results of the study provide input for decision-makers in universities on how to improve employee engagement that will reduce lecturer turnover. Research limitation: The research is limited due to the scope and information gathered only focusing on University X and it does not take into account the individual situation and consideration.